Antimicrobial effect of lining leather fatliquored with the addition of essential oils - Bielak, Elżbieta; Syguła-Cholewińska, Justyna (Wydawnictwo Politechniki Łódzkiej, 2017)
Footwear, especially those often and intensively used, provides an ideal environment for microbial growth. An appropriate high temperature and moisture content inside it enhance bacterial and fungal colonization by microbes. These microorganisms can be potentially pathogenic to human health and responsible for destruction of shoes materials from which the parts inside the shoe are made. In previous studies it has been shown that the addition of essential oils of antiseptic activity at leather finishing operations allows a leather to get antimicrobial properties. The aim of this paper is to assess the durability of antimicrobial effect of leather fatliquored with the addition of cinnamon, thyme and oregano essential oils at concentration of 5% per leather weight. Antimicrobial activity was evaluated according to guidelines of PN-EN ISO 20645:2006 “Textile fabrics – determination of antibacterial activity – Agar diffusion plate test” after 36-month storage. The obtained results have indicated that leathers under investigations show antimicrobial activity against E. coli, S. aureus and C. albicans strains even 3 years after fatliquoring. The use of natural bioactive substances such as cinnamon, thyme and oregano oils at concentration of 5% per leather weight in the leather finishing process may be an alternative to biocides used in the tanning industry as well it can improve hygienic properties of shoes, internal parts of which are made of such finished leathers.
Keywords: lining leathers; essential oils; antimicrobial finish; leather hygienic properties; skóry podszewkowe; olejki eteryczne; wykończenie antybakteryjne; skóra- właściwości higieniczne